Interventional cardiology and cardiac surgery in India. Issue 3 (14th February 2008) - Chaturvedi, V; Talwar, S; Airan, B; Bhargava, B
Abstract : In India, as is happening world wide, the use of coronary interventions is likely to maintain the pace of growth seen in the past decade. This will be facilitated by better access to experienced cardiologists and catheterisation laboratories across the country. Similar growth has occurred in cardiovascular surgery despite constraints of infrastructure and affordability. Cardiovascular research established four decades ago is being carried forward with provision of indigenous technology equal to the best in the world, but tailored to local need and affordability.